(untitled) (Journal of Academic Research, 2021)
This research aims to determine the climatic features of the forty winters in the northwestern region of Libya, which represent a long cold wave that extends from December 25 to February 2 by analyzing the daily climatic data for Those 40 days divided into two periods: The White Nights that start from December 25 to January 13, and the Black Nights that extends from January 14 to February 2 according to Libyan Folklore., The average of two periods of the forty Nights was compared by using the t-test to detect the direction of change in the minimum temperature And whether the differences are statistically significant, and identifying short cold waves during the forty-winter period for the period 2008-2020, and The results revealed that the occurrence of 65 cold waves during the white nights period, and 54 cold waves between 23 short waves, 27 medium waves, and 4 long waves during the period of Black Nights. In addition to the emergence of different trends for the minimum temperature during the two winter forties, and the direction of change was at a statistical significance level less than 0.05 in some climatic stations.